2016
DOI: 10.1177/1367006916632302
|View full text |Cite
|
Sign up to set email alerts
|

The adjective in Dutch-French codeswitching: Word order and agreement

Abstract: Aims and Objectives: This paper investigates the word order and adjectival agreement patterns in French-Dutch codeswitched Determiner Phrases (DPs). It examines the predictions made by two theoretical points of view: the approach by MacSwan (2009) within the Minimalist Program (MP) and the Matrix Language Framework (MLF) (Myers-Scotton & Jake, 2009).Methodology: The predictions of these frameworks are compared to data gathered in a grammaticality judgment task. In total, 120 codeswitched sentences were present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 28 publications
(38 reference statements)
2
13
0
Order By: Relevance
“…In general, Welsh-English code-switching data show clear regularities, with Welsh grammar determining word order in bilingual clauses with very few exceptions (see Deuchar et al, 2018). However, due to the generally low occurrence of attributive adjectives in production data, determining the grammatical constraints that may predict code-switching patterns has been the focus of attention of many studies, not only on Welsh-English code-switching (Parafita Couto et al, 2015, 2017 but also on adjective-noun code-switching in other language pairs where the switch point also constitutes a conflict site (e.g., Spanish-English, Papiamento-Dutch, or French-Dutch). Most of these studies examined patterns of adjective-noun switching in different bilingual populations and using different methodologies, to evaluate the predictions of two theoretical accounts: the Matrix Language Framework (MLF, Myers-Scotton, 1993) and the Minimalist Programme approach (MP, Cantone and MacSwan, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, Welsh-English code-switching data show clear regularities, with Welsh grammar determining word order in bilingual clauses with very few exceptions (see Deuchar et al, 2018). However, due to the generally low occurrence of attributive adjectives in production data, determining the grammatical constraints that may predict code-switching patterns has been the focus of attention of many studies, not only on Welsh-English code-switching (Parafita Couto et al, 2015, 2017 but also on adjective-noun code-switching in other language pairs where the switch point also constitutes a conflict site (e.g., Spanish-English, Papiamento-Dutch, or French-Dutch). Most of these studies examined patterns of adjective-noun switching in different bilingual populations and using different methodologies, to evaluate the predictions of two theoretical accounts: the Matrix Language Framework (MLF, Myers-Scotton, 1993) and the Minimalist Programme approach (MP, Cantone and MacSwan, 2009).…”
Section: Introductionmentioning
confidence: 99%
“… Vanden Wyngaerd (2017) examined the predictions made by an MP approach ( Cantone and MacSwan, 2009 ) and the MLF regarding both word order as well as adjectival agreement patterns in French–Dutch mixed nominal constructions. In Dutch, adjectives occur pre-nominally, whilst adjectives are predominantly post-nominal in French, thus allowing for a direct contrast of both models.…”
Section: Introductionmentioning
confidence: 99%
“…Some comparative analyses addressing the question of adjective-noun order in codeswitched noun phrases have been done couched within the two theoretical models (MP and MLF) but with different outcomes (cf. Parafita Couto et al, 2015Parafita Couto & Gullberg, 2017;vanden Wyngaerd, 2017). Of the two models in question, Myers-Scotton's (2002) MLF differentiates the languages involved: one language is known as the matrix language (ML); and the other as the embedded language (EL).…”
Section: Introductionmentioning
confidence: 99%
“…However, scholars do not agree on the best theoretical account of these regularities. Recently, an interest has emerged in evaluating the predictions of theoretical models to try to disentangle between theoretical predictions (see Blokzijl, Deuchar, & Parafita Couto, 2017; Eppler, Luescher, & Deuchar, 2017; Fairchild & Van Hell, 2017; Herring, Deuchar, Parafita Couto, & Moro Quintanilla, 2010; Parafita Couto, Boutonnet, Hoshino, Davies, Deuchar, & Thierry, 2017; Parafita Couto, Deuchar, & Fusser, 2015; Parafita Couto & Gullberg, 2017; vanden Wyngaerd, 2017). These researchers have shown that different theories account for some aspects of the observed data, but there is no overarching theory that can explain all the code-switching patterns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation